2005
DOI: 10.4049/jimmunol.174.9.5298
|View full text |Cite
|
Sign up to set email alerts
|

An Important Role of CD80/CD86-CTLA-4 Signaling during Photocarcinogenesis in Mice

Abstract: Although previous studies have shown that altered B7 costimulation plays a critical role in UV irradiation-induced regulation of immunity, the individual roles of the B7 receptors (CD28 and CTLA-4) or the B7 family members (CD80 and CD86) have not been explored. Thus, we investigated CTLA-4 signaling during photocarcinogenesis of chronically UV-B-exposed mice using an antagonistic anti-CTLA-4 Ab. Anti-CTLA-4-treated mice developed significantly fewer UV-induced tumors. Moreover, anti-CTLA-4 treatment induced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…It remains to be determined how the PUVA-induced regulation of the disturbance of the IL-17/23 axis and the iTregs relate to carcinogenesis upon long-term treatment (54,55). Interestingly, upon chronic UV exposure, Tregs were found to be involved in skin cancer formation in mice (31) and are targeted in human cancer immunotherapy (28). In contrast, IL-23 and IL-17 are increased in human tumors and have been implicated in causing cancer (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be determined how the PUVA-induced regulation of the disturbance of the IL-17/23 axis and the iTregs relate to carcinogenesis upon long-term treatment (54,55). Interestingly, upon chronic UV exposure, Tregs were found to be involved in skin cancer formation in mice (31) and are targeted in human cancer immunotherapy (28). In contrast, IL-23 and IL-17 are increased in human tumors and have been implicated in causing cancer (56).…”
Section: Discussionmentioning
confidence: 99%
“…Data from earlier studies indicated that treatment of mice with CTLA4Ig, a soluble form of CTLA4 that effectively blocks CD80/CD86 engagement with CD28, suppressed antitumor immunity, transplant rejection, and autoimmune responses (30). Moreover, blocking CTLA4 signaling has been shown to inhibit the suppressive function of UV-induced CD4 + CD25 + T cells (31). We therefore used anti-CTLA4 mAb treatment to test the functional relevance of PUVAinduced Tregs.…”
Section: Ctla4 Signaling Is Crucial For Puva-induced Treg Functionmentioning
confidence: 99%
“…For instance, UVB irradiation induces a specific subset of UV regulatory T-cells, which have been shown to suppress effector T-cell responses via IL-10. [109][110][111][112][113] UVB radiation has also been reported to inhibit the Ag-presenting function of dendritic cells, i.e., epidermal Langerhans cells, directly via UVB-induced cytotoxicity as well as indirectly via the release of immunosuppressive cytokines. 114,115 Intriguingly, our recent experiments have demonstrated, that cbl-b -/-mice reject implanted TC-1 tumors as well as spontaneous UVB-induced skin tumors.…”
Section: Cbl-b -/-Mice Display Enhanced Immune Surveillance and Spontmentioning
confidence: 99%
“…The most common negative effect is acute sunburn or erythema, but UV insults can also lead to premature photoaging [17][18][19][20][21][22] and carcinogenesis [23][24][25][26][27][28][29]. The identification of novel treatments to increase skin resistance to UV induced damage without the limitations of traditional methods would prove particularly useful.…”
Section: Discussionmentioning
confidence: 99%